2013
DOI: 10.1139/cjm-2013-0614
|View full text |Cite
|
Sign up to set email alerts
|

Serotype distribution of invasive Streptococcus pneumoniae in Canada after the introduction of the 13-valent pneumococcal conjugate vaccine, 2010–2012

Abstract: The introduction of the 7-valent pneumococcal vaccine (PCV7) in Canada was very effective in reducing invasive pneumococcal disease (IPD) in children; however, increases of non-PCV7 serotypes have subsequently offset some of these reductions. A 13-valent pneumococcal vaccine (PCV13) targeting additional serotypes was implemented between 2010 and 2011, and in 2012 changes in the incidence of disease and the distribution of IPD serotypes began to emerge. The incidence of IPD in children <5 years of age declined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 42 publications
6
58
1
2
Order By: Relevance
“…6,7,19,24 Notably, this universal observation of replacement in carriage was associated with an overall marked reduction in pneumococcal disease, indicating that most replacement serotypes are less invasive strains with a lower disease potential. 10,19,25,32,33 While overall-pneumococcal carriage rates were stable following PCV introduction in several reports, 7,24,34 a similar reduction to that observed in our study was found in a rural South African community 35 and among American Indian children <5 years old. 36,37 In France, PCV introduction resulted in a significant reduction in overall-pneumococcal carriage among children with otitis media, 28 and children with pneumonia, but not in healthy children [personal communication, Robert Cohen].…”
Section: Discussionsupporting
confidence: 90%
“…6,7,19,24 Notably, this universal observation of replacement in carriage was associated with an overall marked reduction in pneumococcal disease, indicating that most replacement serotypes are less invasive strains with a lower disease potential. 10,19,25,32,33 While overall-pneumococcal carriage rates were stable following PCV introduction in several reports, 7,24,34 a similar reduction to that observed in our study was found in a rural South African community 35 and among American Indian children <5 years old. 36,37 In France, PCV introduction resulted in a significant reduction in overall-pneumococcal carriage among children with otitis media, 28 and children with pneumonia, but not in healthy children [personal communication, Robert Cohen].…”
Section: Discussionsupporting
confidence: 90%
“…Whilst vaccination has had success in reducing the burden of disease caused by vaccine-type S. pneumoniae (Huss et al, 2009;Bonten et al, 2015), ongoing surveillance is important to monitor trends in serotype distribution as the benefits of vaccination could be offset by increased rates of pneumococcal disease caused by nonvaccine serotypes (Hicks et al, 2007;Weinberger et al, 2011;Demczuk et al, 2013;Zuccotti et al, 2014). Recently, the 13-valent pneumococcal conjugate vaccine was shown to reduce CAP and IPD caused by vaccine-type pneumococci in healthy adults, prompting a renewed interest in monitoring S. pneumoniae serotype distribution in Canadian adult populations (Bonten et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Following the introduction of PCV13 as a three-dose primary schedule at 2, 4 and 6 months of age and a booster dose at 12 --15 months in 2010/2011 in Canada, the prevalence of the 13 vaccine serotypes declined significantly from 2010 to 2012: from 66% (224/339) to 41% (101/244, p < 0.001) in children < 5 years of age and from 54% (1262/2360) to 43 % (1006/2353, p < 0.001) in children ‡ 5 years of age [73]. In the UK, following introduction of PCV13 in a two-dose infant schedule at 2 and 4 months and a boost at 12 --15 months, there was a 75% decrease in incidence of invasive disease caused by the six additional vaccine serotypes present in PCV13 in infants < 2 years of age.…”
Section: Impactmentioning
confidence: 99%